2004
DOI: 10.1128/jcm.42.7.3191-3195.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Commercially Available Serologic Assays Used To Detect Human Parvovirus B19-Specific Immunoglobulin M (IgM) and IgG Antibodies in Sera of Pregnant Women

Abstract: A split-sample study was conducted to evaluate the performances of three enzyme immunoassays (EIAs) utilizing one or more conformational antigens to detect human parvovirus B19 (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 19 publications
1
26
0
2
Order By: Relevance
“…It is generally accepted that IgM antibodies are an indicator of an acute or recent infection, and they may remain detectable for up to four months (Jordan, 2000). In contrast, IgG antibodies remain elevated for years, and their presence without detectable IgM is usually interpreted as previous infection (Butchko and Jordan, 2004).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is generally accepted that IgM antibodies are an indicator of an acute or recent infection, and they may remain detectable for up to four months (Jordan, 2000). In contrast, IgG antibodies remain elevated for years, and their presence without detectable IgM is usually interpreted as previous infection (Butchko and Jordan, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…The IgG antibodies to B19 detected by EIA reached a maximum of 137.2 IU/mL in the sample collected at week 22 from symptom onset and paradoxically, in spite of the B19 persistence, declined to the level of 66.5 IU/mL in the week 103 sample. It can be assumed that this antibody decrease is reflecting an earlier disappearance of IgG antibodies to linear epitopes (Manaresi et al, 2004;Butchko and Jordan, 2004). On the other hand, it can be hypothesized that this antibody decrease represents an inability of the immune system to eliminate the virus (Lowry et al, 2005;Kerr et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Commercially available assays for parvovirus B19 have high variation of sensitivity and specificity147-149 that may contribute to the misdiagnosis of hPV B19 infection as measles or rubella 143144 One study clearly reported the variation in specificity between five different commercially available tests for detection of IgM antibodies to hPV B19.The specificities of tests varied between 94% (Ideia; DAKOT A/S, Copenhagen, Denmark) and 70.1% (Parvoscan; EURO Diagnostica, Malmö, Sweden) 147…”
Section: Diagnosismentioning
confidence: 99%
“…Serodiagnostic of B19 infection is mainly based on the detection of antibodies to recombinant structural proteins (VP2 or VP1-2 capsids) produced in eukaryotic expression systems (Table 2) because IgG to these proteins persist for long periods of time in contrast to antibodies to linear, denatured, epitopes of structural proteins, which are short lived . No data available Butchko & Jordan (2004) *No information on the ability of these kits to detect IgG to genotype 2, B19 is available. It was shown recently that genotype 1 antibodies crossneutralize genotype 2 virus (Blumel et al, 2005).…”
Section: B19 Detection and Serodiagnosticsmentioning
confidence: 99%